Palaemon elegans - a new component of the Gulf of Gdańsk macrofauna - Urszula Janas (Oceanologia, 2004)
The present paper reports on the occurrence of the prawn Palaemon elegans Rathke in the coastal waters of the Gulf of Gdańsk in the years 2002-2003, and in other regions of the Baltic Sea as recorded by various authors.